2017
DOI: 10.18869/acadpub.jafm.73.239.26639
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Analysis of Unsteady Aerodynamics and Vehicle Motion of a Passenger Car in Crosswind Condition

Abstract: High-speed passenger car requires a lighter weight for improving power performance and reducing fuel consumption; a car with higher-speed and lighter weight will lead to the passenger car more sensitive to the crosswind, which will affect the stability and drivability of the passenger car. This study employs the fully-coupled method to investigate a passenger car subjected "1-cos" crosswind with consideration of the vehicle motion. Large eddy simulation (LES) and dynamic mesh is adopted to investigate the unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The vehicle model studied in this paper is a 1:1 model of real vehicle, as shown in Figure 2, which we have ever used in a previous study (Huang et al, 2017a(Huang et al, , 2017b. The length of the vehicle is L = 4.587 m and the height is H = 1.467 m, while the width is W = 1.799 m. The frontal projection area of the vehicle is 2.06 m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The vehicle model studied in this paper is a 1:1 model of real vehicle, as shown in Figure 2, which we have ever used in a previous study (Huang et al, 2017a(Huang et al, , 2017b. The length of the vehicle is L = 4.587 m and the height is H = 1.467 m, while the width is W = 1.799 m. The frontal projection area of the vehicle is 2.06 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…where C S is the model coefficient, which is set to be 0.1 according to the research of Huang et al (2017aHuang et al ( , 2017b, D denotes the filter width and f d is expressed by the Van Direst damping function as follows: Vehicle stability in crosswind…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Aerodynamic lift is sensitive to airflow distribution around the car underbody. However, most works under crosswind condition had been confined to a simplified model which did not consider the effect of underbody details on aerodynamic force, [7][8][9][10][11] and the influence of underbody structure under no-crosswind is such that it changed flow field, which could be lead to the aerodynamic force changing. For example, Gorre et al 12 showed that there was a considerable air resistance due to underbody components.…”
Section: Introductionmentioning
confidence: 99%